Dampak Pembelajaran Daring pada Siswa Kelas 5 SD Negeri Tegalrejo Khususnya pada Minat Baca Buku Cetak - Fitra Amaldi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the impact of online learning on 5th grade students of SDNegeri Tegalrejo, especially on interest in reading printed books. This research applies aqualitative case study. Data were collected using a questionnaire from Google Form andsemi-structured interviews. The sample used in this study were 15 parents of 5th gradeelementary school students in Tegalrejo. The results of the research that has beenconducted, show that online learning has an impact on 5th grade students of SDNTegalrejo, especially on interest in reading printed book. It is proven by the results of thepercentage of parental responses that have been processed in this study.